The Effect of Higher Order Thinking Skill (HOTS) Based Student Worksheets (LKPD) on Science Learning Outcomes in Grade V Students of SD MIS YPI BTG. Quiz - Adella, Sindy; Siregar, Nurdiana (Journal of English Language and Education, 2025)
This study aims to determine the effect of the use of Student Worksheets (LKPD) based on Higher Order Thinking Skills (HOTS) on the learning outcomes of Natural Sciences (IPA) students in grade V at MIS YPI Btg Quiz. LKPD is designed to hone the ability to analyze, evaluate, and solve problems according to learning achievement indicators. The research used an experimental method with a two-group pretest - posttest design. The research population is all students of class V MIS YPI Btg Quiz which totals 55 students, while the research sample consists of class VA (29 students) and class VB (26 students) in the even semester of the 2024/2025 academic year. The research instrument was in the form of a description test totaling 5 items that had been validated (r count 0.458 - 0.730 r table 0.278) and reliable (Cronbachs Alpha = 0.637). The results showed that there was a significant difference between the science learning outcomes of students who used HOTS-based LKPD and those who did not use it. The independent samples t-test obtained a value of Sig. (2-tailed) = 0.001 ( 0.05), so it can be concluded that the application of HOTS-based LKPD has a real effect on improving the science learning outcomes of grade V students.